2011
DOI: 10.1371/journal.pone.0016636
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Profiling of Primary Colorectal Carcinomas and Liver Metastases Identifies LEF1 as a Prognostic Biomarker

Abstract: PurposeWe sought to identify genes of clinical significance to predict survival and the risk for colorectal liver metastasis (CLM), the most common site of metastasis from colorectal cancer (CRC).Patients and MethodsWe profiled gene expression in 31 specimens from primary CRC and 32 unmatched specimens of CLM, and performed Significance Analysis of Microarrays (SAM) to identify genes differentially expressed between these two groups. To characterize the clinical relevance of two highly-ranked differentially-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 49 publications
(62 reference statements)
4
48
2
1
Order By: Relevance
“…LEF-1, a member of the LEF1/TCF transcription factor family involved in the Wnt pathway, is a DNA binding transcription factor that functions by recruiting β-catenin to Wnt target genes for regulation. It has recently been reported that levels of LEF1 are markedly correlated with tumor cell invasion and patient prognosis (31)(32)(33)(34). Certain members of the MMP family (MMP-2, -7, -9 and -26) have been identified as downstream target-genes of the LEF1/ TCF complex.…”
Section: Discussionmentioning
confidence: 99%
“…LEF-1, a member of the LEF1/TCF transcription factor family involved in the Wnt pathway, is a DNA binding transcription factor that functions by recruiting β-catenin to Wnt target genes for regulation. It has recently been reported that levels of LEF1 are markedly correlated with tumor cell invasion and patient prognosis (31)(32)(33)(34). Certain members of the MMP family (MMP-2, -7, -9 and -26) have been identified as downstream target-genes of the LEF1/ TCF complex.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies used home-made cDNA microarrays [8], [13], one used the Agilent human 1A platform [9], and the last one used home-spotted chips using the Sigma human Oligolibrary [11]. Because these platforms did not use Affymetrix probes, we first converted our probe signature into a gene signature.…”
Section: Resultsmentioning
confidence: 99%
“…The red and green bars bellow the heatmap indicate the hepatic metastasis samples from the GIST and the SCC respectively. C) Normal liver tissues (light blue), primary tumors (green) and hepatic metastases (red) were clustered using the 24 genes of our 33-gene signature present in Lin et al [8] study. D) Normal colon tissues (blue), primary tumors (green), hepatic metastases (red) and peritoneal carcinomatosis (orange) were clustered using the 32 genes of our 33-gene signature present in Kleivi et al [9] study.…”
Section: Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations